Sulfatide Inhibits HMGB1 Secretion by Hindering Toll-Like Receptor 4 Localization Within Lipid Rafts - Kim, Hee Sue; Han, Myeonggil; Park, In Ho; Park, Cheol Ho; Kwak, Man Sup; Shin, Jeon-Soo (Frontiers in Immunology, 2020)
The high mobility group box 1 (HMGB1) is a well-known late mediator of sepsis, secreted by multiple stimuli, involving pathways, such as the mitogen-activated protein kinase (MAPK) and nuclear factor kappa B (NF-κB) pathways, and reactive oxygen species (ROS) under inflammation. Sulfatide, in contrast, is a sphingolipid commonly found in myelin sheets with a disputed immunological role. We sought to determine the immunological characteristics of sulfatide in the periphery by analyzing the secretion of HMGB1 triggered by lipopolysaccharide (LPS) stimulation in Raw 264.7 cells. Suppression of HMGB1 secretion by inhibiting its cytosolic translocation was observed after pre-treatment with sulfatide before LPS stimulation. Further analysis of the downstream molecules of toll-like receptor (TLR) signaling revealed suppression of c-Jun N-terminal kinase (JNK) phosphorylation and p65 translocation. LPS-mediated ROS production was also decreased when sulfatide pre-treatment was provided, caused by the down-regulation of the phosphorylation of activators, such as IRAK4 and TBK1. Investigation of the upstream mechanism that encompasses all the aforementioned inhibitory characteristics unveiled the involvement of lipid rafts. In addition to the co-localization of biotinylated sulfatide and monosialotetrahexosylganglioside, a decrease in LPS-induced co-localization of TLR4 and lipid raft markers was observed when sulfatide treatment was given before LPS stimulation. Overall, sulfatide was found to exert its anti-inflammatory properties by hindering the co-localization of TLR4 and lipid rafts, nullifying the effect of LPS on TLR4 signaling. Similar effects of sulfatide were also confirmed in the LPS-mediated murine experimental sepsis model, showing decreased levels of serum HMGB1, increased survivability, and reduced pathological severity.